PENGARUH ELECTRONIC WORD OF MOUTH DAN KEPERCAYAAN KONSUMEN TERHADAP MINAT BELI PADA LAZADA (Survei Pada Mahasiswa Universitas Perjuangan Angkatan 2018) - Novia Reski Kurnia (Exchall: Economic Challenge, 2022)
The purpose of this study was to determine and analyze (1) the effect of Electronic Word Of Mouth, consumer trust, and buying interest on Lazada surveys of University of Perjuangan students batch 2018; (2) The Effect of Consumer Confidence on Buying Interest on Lazada, a survey of 2018 Perjuangan University students simultaneously; (3) The Effect of Electronic Word Of Mouth, and Consumer Trust on Lazada Buying Interest, a partial survey of 2018 Perjuangan University students. The method used in this research is the Causality Method. The analysis tool uses multiple linear regression. The data used is primary data. Based on the results of the study, it is known that the influence of Electronic Word Of Mouth and consumer trust simultaneously has a significant effect on Lazada Buying Interest users at Universitas Perjuangan. Partial direct trust has a significant effect on Buying Interest. Keywords: Electronic Word Of Mouth, Consumer Trust, Buying Interest